Cultural scripts surrounding young people's sexual and romantic relationships in the Western Highlands of Guatemala. Issue 9 (1st September 2016) - Singleton, Robyn; Schroffel, Heidi; Findlay, Trinity; Winskell, Kate
Abstract: Guatemala has one of the world's highest teenage pregnancy rates and 92% of young people report not using contraception for first sex. We conducted narrative-based thematic analysis of a sample of narratives ( n = 40; 15 male-authored, 25 female-authored) on HIV and sexuality, submitted to a 2013 scriptwriting competition by young people aged 15–19 years from Guatemala's Western Highlands. Our objective was to identify dominant cultural scripts and narratives that deviated positively from that norm with a view to informing the development of educational curricula and communication materials promoting youth sexual and reproductive health. The narratives are characterised by romantic themes and melodramatic plotlines: three in four had tragic endings. Rigid gender norms and ideologies of enduring love make female characters blind to the potential consequences of unprotected sex and vulnerable to betrayal and abandonment. Unprotected sex is the norm, with contraception and sexually transmitted infection protection mentioned rarely. In the four positively deviant narratives, female and male characters' interaction is based on mutual respect, dialogue and genuine affection. The narratives reveal opportunities for action to increase sexual health knowledge and access to services and to challenge harmful cultural scripts, potentially by leveraging the positive value attached to romantic love by authors of both sexes.